Peningkatan Pengetahuan Dan Ketrampilan Prenatal Exercise Pada Ibu Hamil Untuk Persiapan Persalinan Di Desa Nambo Tahun 2025 - Hariandja, Andy Martahan Andreas; Achwan, Achwan; Attala, Ceiza; Syafi'i, Dyan; Albar, Ibnu; Astri, Jasya; Daffa, Muhammad; Khansa, Syafinka (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Background: Pregnancy is a physiological process that causes various changes in the mother's body, including hormonal and metabolic changes that can cause discomfort and the risk of complications if not managed properly. One effective way to maintain the health of pregnant women is through prenatal exercise. Objective: This study aims to improve the health and fitness of pregnant women through the role of prenatal exercise, so that it can help reduce the risk of physical disorders during pregnancy and prepare the body for a smoother delivery. Method: The activity method carried out begins with socialization to the community and identification of health problems of pregnant women through examination of vital signs, height, weight, and measurement of muscle strength and flexibility. Furthermore, counseling is provided on the benefits and techniques of prenatal exercise. Prenatal exercise is carried out in a structured manner with movements that are adjusted to the condition of pregnancy. Program evaluation is carried out through measuring fitness levels before and after the intervention, as well as participant satisfaction surveys. Results: The results of the study showed that prenatal exercise improved fitness, strength and flexibility for pregnant women as evidenced by a significant increase in pre-test scores compared to post-test. Conclusion: Increasing knowledge and skills in prenatal exercise has a positive impact on increasing endurance in pregnant women, increasing muscle flexibility and muscle elasticity, and increasing knowledge of pregnant women about physiotherapy during pregnancy.